Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 411 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Animalia", "Geometry POLYGON((-97.413024 18.661858,-97.514648 18.669665,-97.599792 18.698285,-97.619018 18.789317,-97.640991 18.841313,-97.564086 18.888096,-97.481689 18.872503,-97.388305 18.817917,-97.360839 18.773715,-97.360839 18.690480,-97.413024 18.661858))" ] } The dataset includes 411 records from 25 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002297-150512124619364/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences